PENGARUH DESAIN PEKERJAAN DAN BUDAYA KERJA TERHADAP KINERJA KARYAWAN PEMASARAN MELALUI KEPUASAN KERJA KARYAWAN PT NYONYA MENEER SEMARANG - Nurul Fidiyah; Nawazirul Lubis; Reni Shinta Dewi (Universitas Diponegoro, 2015)
Marketing job performance its achievements sales target that was determined in accordance with. Design a good job, work culture that appropriate and job satisfaction, will be able to increase performance marketing. But the achievement results sales that is not suitable target and decreased if compared with previous period is still happen. This Research using census sampling techniques to 56 marketing employees of PT Nyonya Meneer Semarang by using this method interview and instrument data collection questionnaire and guiding interview. Data analyzed in qualitative and quantitative with through tests the validity, and trial reliability. While data analysis done by using regression analysis simple linear regression, multiple linear regression, t-test, F test, path analysis and sobel test. Results of the study showed that job design and work culture significantly affect satisfaction to work and performance. Based on the results count analysis of the line and sobel test showed that the job satisfaction employees is a partial variable mediation between the job design and work culture and suggestions to employees performance that was given. should also be able to build a relationship a harmonious relationship with the owner outlet jamu (northen outlet) that will be able to increase sales PT Nyonya Meneer Semarang.